Analisis dan Perancangan Sistem Manajemen Inventaris Menggunakan Metode Fishbone - Hijrah Hijrah; Maulidar Maulidar (Universitas Merdeka Malang, 2021)
This research was conducted with a qualitative approach and conducted interviews, observations, and documentation review to obtain primary data and secondary data. The data obtained from the research stages will be analyzed using the fishbone method to obtain the root of the problem by looking at the causes and effects of these problems. After all stages of the analysis are carried out, it will be recommended applications that can help business companies engaged in internet services minimize losses due to excess stock. The recommended application is designed using information system design tools or methods that describe the system flow, data structure, and related relationships to facilitate the application and development of applications. From the results of the analysis of the research conducted, it can be concluded that the inventory design is needed so that an inventory application is designed according to the needs of the company